Discrimination of early pregnancy and endometrial cyst by ultrasonographic assessment of uterine echotexture in mares - Abuzer Kafar ZONTURLU; Tugra AKKUS; Cihan KACAR; Omer KORKMAZ; Semra KAYA; Murat Can DEMİR; Birten EMRE (Kafkas Universitesi Veteriner Fakültesi Dergisi, 2018)
The present study was performed to demonstrate the tissue differentiation of uterine ultrasonographic image by computer assisted analysis programs in mares with endometrial cyst and early pregnancy. A total of 124 thoroughbred Arabian mares were used in the study, with early pregnancy and endometrial cyst. Mares were divided into six groups according to stage of early pregnancy (Group I, n=12 (13th day pregnancy); Group II, n=15 (14th day pregnancy); Group III, n=29 (15th day pregnancy); Group IV, n=17 (16th day pregnancy); Group V, n=12 (17th day pregnancy)) and as endometrial cysts (Group VI, n=39). The mean gray value (MGV), heterogeneity (HET) and contrast (CON) of the uterine images that were recorded during ultrasound scan were measured through computer assisted program. The MGV values of the echotexture parameters were significantly higher in the pregnant mare (55.20±4.95, 58.31±3.88, 56.23±1.88, 54.15±3.47 and 56.08±2.94, respectively) than the endometrial cyst mares (42.71±0.71) (P<0.001). The HET values were significantly higher in the pregnant mare (20.75±1.53, 19.23±1.39, 21.42±0.88, 22.37±1.32 and 22.20±1.09, respectively) than the endometrial cyst mares (15.06±0.44) (P<0.001). CON values were lower in pregnant mare (152.83±7.02, 144.02±8.18, 141.03±4.83, 145.93±4.70 and 154.65±4.86 respectively) than endometrial cyst mare (191.35±3.97) (P<0.001). As a result; it has been concluded that the measurement values of echotexture parameters (MGV, HET, CON) may be important reference criteria when early pregnancy and endometrial cyst are distinguished in mare, which can often cause misconception.